Effect of Successive In-office Bleaching Sessions on the Surface Properties, Substance Loss, Biaxial Flexural Strength, and Reliability of CAD-CAM Monolithic Materials - Queiroz, J. F. C. [UNESP]; Fernandes, L. [UNESP]; Dovigo, L. N. [UNESP]; Fonseca, R. G. [UNESP] (Operative Dentistry Inc, 2023)
Little is known about the effects of in-office bleaching on the surface properties and on other aspects of CAD-CAM monolithic materials, especially when successive bleaching sessions are conducted. This study evaluated the effect of up to three successive in-office bleaching sessions on the microhardness, roughness, topography, substance loss, biaxial flexural strength (BFS), and reliability of CAD-CAM monolithic materials. Disks from Lava Ultimate (LU), Vita Enamic (VE),and IPS Empress CAD (EMP) were fabricated and submitted to one, two, and three bleaching sessions. In-office bleaching was performed with 40% hydrogen peroxide and each session consisted of three applications of 20 minutes each. The analyses regarding the aforementioned parameters were assessed before and after the first, second, and third bleaching sessions, except for BFS, which was evaluated at the baseline and after the third session. Weibull modulus was calculated from the BFS data. Bleaching decreased the microhardness of LU and VE from the third and second sessions, respectively, and affected neither the roughness nor the BFS of the three materials. However, in LU, it decreased the reliability and caused topographic changes, which were accentuated by the increase in the number of sessions. In general, LU and EMP showed, respectively, the highest and the lowest substance losses. Successive in-office bleaching sessions with the use of the protocol of the present study should be avoided in LU and VE.